Pengembangan Sistem Informasi Monitoring Pengadaan Barang Atau Jasa Berbasis Website Dengan Metode Rational Unified Process (RUP) (Studi Kasus : Unit Bisnis Jasa O & M 2 Luar Jawa PT PJB Surabaya) - M Bayu Dwi Nugroho; Mochammad Chandra Saputra; Djoko Pramono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Business Operation Service Unit & Maintenance Outside Java - 2 (UJLJ-2) is one of the unit in PT PJB Surabaya which has the tasks of doing the procurement process of goods or services in providing electrical infrastructure proposed by a special power plant unit outside of Java which has been approved by PT PLN. But in performing these tasks there are some obstacles such as data collection procurement that has not been integrated between divisions, monitoring data procurement by managers that must meet the employees who brought the data first and units from outside Java to know the progres conditions of their procurement being handled by UJLJ-2, they still ask by calling UJLJ-2 by phone first. Therefore, the information system is needed to handle the problem. The integrated procurement data collection process between divisions, data monitoring and procurement progress can be simplified by using the Procurement Monitoring Information System (SIMOP) built with Rational Unifed Process (RUP) method that is done in the inception, elaboration, construction and transition phases. Testing the system is done with blackbox validation testing with 5 test cases to test the functional requirements of the system with 100% results Valid and compability testing to test the non-functional requirements obtained 2 critical issues results. UAT testing is used to detect the user acceptance towards the system which has been built and get the value accaptance of 96.6% for the actor manager, 80% for actor staff of unit outside Java island , 88.3% for actor staff of planner division , 73.30% for actor staff of producer , and 70% for for actor staff of administration division.